2001
DOI: 10.1111/j.1348-0421.2001.tb01287.x
|View full text |Cite
|
Sign up to set email alerts
|

Stenotrophomonas maltophilia Interaction with Human Epithelial Respiratory Cells In Vitro

Abstract: Bacteria of Stenotrophomonas maltophilia have been isolated with increasing frequency from the airways of cystic fibrosis (CF) patients, usually following P. aeruginosa infections, but their adherence to human epithelial respiratory cells has never been investigated. In this study, various S. maltophilia strains were seen to adhere to epithelial respiratory cells in vitro, mainly along intercellular junctions. Bacteria could also enter into host cells, as determined by the gentamicin exclusion assay and transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Transmission electron microscopy indicates that both cystic fibrosis (CF) and non-cystic fibrosis (NCF) S. maltophilia isolates adhere to and are able to invade transformed human bronchial epithelial 16 HBE14oϪ cells (Fig. 5) (73). No significant difference between the adherences of CF and NCF isolates to host bronchial cells was observed.…”
Section: Adherence To and Invasion Of Host Cellsmentioning
confidence: 95%
See 2 more Smart Citations
“…Transmission electron microscopy indicates that both cystic fibrosis (CF) and non-cystic fibrosis (NCF) S. maltophilia isolates adhere to and are able to invade transformed human bronchial epithelial 16 HBE14oϪ cells (Fig. 5) (73). No significant difference between the adherences of CF and NCF isolates to host bronchial cells was observed.…”
Section: Adherence To and Invasion Of Host Cellsmentioning
confidence: 95%
“…maltophilia can form biofilms on lung cells (73,83,268). Confocal microscopy of biofilms formed by CF isolate S. maltophilia OBGTC9 on CF sputum-derived bronchial epithelial IB3-1 cell monolayers revealed that S. maltophilia formed microcolonies embedded in a matrix (268).…”
Section: Molecular Mechanisms Involved In Pathogenesis Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasion of epithelial respiratory cells was recently reported for S maltophilia CF clinical isolates (8). Uptake of our S maltophilia strains by A549 cells was assessed carrying out exclusion experiments with a combination of antibiotics (amikacin and ceftazidime) that we proved to be effective in selectively eliminating extra-cellular bacteria.…”
Section: Molecular Detection Ofvirulence Related Genesmentioning
confidence: 99%
“…S. maltophilia strains of environmental and clinical origin have been shown to be able to adhere to and to invade cultured epithelial respiratory cells, as well as to adhere to different abiotic surfaces with production of biofilm (5,8).…”
mentioning
confidence: 99%